FATORES DE SOBREVIVÊNCIA DE EMPRESAS EXECUTORAS DE SERVIÇOS DE OBRAS PAULISTAS - Silva, Matheus Henrique Dalboni Basilio da; Haito, Ricardo Oviedo; Cardoso, Francisco Ferreira (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Financial and economic crises are detrimental for several members in the construction market. However, there are differences among how its outcomes affect each agent in their production systems. A consequence of this is the closing, bankruptcy, or the migration of some companies to other markets, being the small and micro enterprises (SMEs) more vulnerable to this kind of oscillations. Among the SMEs in construction industry are the trade and specialty contractors (EES), responsible for most of the work in construction sites. Despite of there are several strategies to keep firms competitive and working on financial difficulties in the crises, there is no script or manual to choose the best solution for EES' survival. The aim of this paper is to contribute to the knowledge of how the EES survive in economic downturns. For that purpose, three representatives of three different EES were interviewed in the State of São Paulo, Brazil, using the so-called grounded description approach of Grounded Theory research. As a result, survival factors related to three aspects (product, production and relationships) were identified. Managing those factors can help EES to better understand how to organize themselves in front of economic downturns, as the current context in Brazilian economy.